Characterization of Si : O : C : H films fabricated using electron emission enhanced chemical vapour deposition - Durrant, Steven F. [UNESP]; Rouxinol, Francisco P. M.; Gelamo, Rogerio V.; Transferetti, B. Claudio; Davanzo, C. U.; De Moraes, Mario A. Bica (Elsevier B.V. Sa, 2008)
Silicon-based polymers and oxides may be formed when vapours of oxygen-containing organosilicone compounds are exposed to energetic electrons drawn from a hot filament by a bias potential applied to a second electrode in a controlled atmosphere in a vacuum chamber. As little deposition occurs in the absence of the bias potential, electron impact fragmentation is the key mechanism in film fabrication using electron-emission enhanced chemical vapour deposition (EEECVD). The feasibility of depositing amorphous hydrogenated carbon films also containing silicon from plasmas of tetramethylsilane or hexamethyldisiloxane has already been shown. In this work, we report the deposition of diverse films from plasmas of tetraethoxysilane (TEOS)-argon mixtures and the characterization of the materials obtained. The effects of changes in the substrate holder bias (Vs) and of the proportion of TEOS in the mixture (XT) on the chemical structure of the films are examined by infrared-reflection absorption spectroscopy (IRRAS) at near-normal and oblique incidence using unpolarised and p-polarised, light, respectively. The latter is particularly useful in detecting vibrational modes not observed when using conventional near-normal incidence. Elemental analyses of the film were carried out by X-ray photoelectron spectroscopy (XPS), which was also useful in complementary structural investigations. In addition, the dependencies of the deposition rate on Vs and XT are presented. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: TEOS; Si : O : C : H thin film; EEECVD; PECVD; FTIR; XPS